2022
DOI: 10.3390/molecules27154813
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Tetrastigmae Radix from Two Different Habitats Based on Simultaneous Determination of Multiple Bioactive Constituents Combined with Multivariate Statistical Analysis

Abstract: Tetrastigmae Radix, also known as Sanyeqing (SYQ) in Chinese, is an important traditional Chinese medicine with a long history. Tetrastigma hemsleyanum Diels et Gilg mainly grows in the south of the Yangtze River and is widely distributed. The content of bioactive constituents in SYQ varies greatly in different habitats, and there are obvious differences in the content of bioactive constituents between southwestern SYQ (WS) and southeastern SYQ (ES). To distinguish and evaluate the quality of ES and WS, an ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The results indicated that the highest content of flavonoids, total phenols, and polysaccharides was found in the fibrous roots, followed by the leaves, and was the lowest in the tubers. Currently, the content of flavonoids, 28 phenolic acids, 29 and polysaccharides 28 is commonly used as a quality evaluation index of T. hemsleyanum, 30 providing a theoretical basis for subsequent selection and breeding. In this article, the names of different types of compounds and the cracking process are mainly clarified, but the quality markers of T. hemsleyanum are not reflected in this article.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the highest content of flavonoids, total phenols, and polysaccharides was found in the fibrous roots, followed by the leaves, and was the lowest in the tubers. Currently, the content of flavonoids, 28 phenolic acids, 29 and polysaccharides 28 is commonly used as a quality evaluation index of T. hemsleyanum, 30 providing a theoretical basis for subsequent selection and breeding. In this article, the names of different types of compounds and the cracking process are mainly clarified, but the quality markers of T. hemsleyanum are not reflected in this article.…”
Section: Resultsmentioning
confidence: 99%
“…Te validity of the approach was confrmed through assessments of its linearity, intraday and interday precision, repeatability, stability, recovery, and matrix efect [32]. Te standard curve was established by serial dilution of mixed standards, and the equation for linear regression, coefcient of correlation, and range for linearity was computed.…”
Section: Validation Of the Methodmentioning
confidence: 99%
“…Te majority of studies have concentrated on the quantitative and qualitative analysis of favonoids with signifcant pharmacological efects and high content in a single species. However, it is widely recognized that the efcacy of TCMs is the outcome of the integrated adjustment of multiple components [31,32], emphasizing the need for ensuring the quality of TCMs to achieve their remarkable clinical efects. Yin et al [34] established a method based on UFLC-QTRAP-MS/MS technology for simultaneous determination of multiple active components in Abelmoschi Corolla, which provided an objective method reference for comprehensive evaluation and comprehensive control of Abelmoschi Corolla internal quality.…”
Section: Gra Of Samples Grey Correlation Degree Analysismentioning
confidence: 99%
“…It is worth noting that only one study reported the isolation of flavonoids from the ethyl acetate layer of LBR [11]. This discrepancy may be attributed to the significant variation in the content of bioactive constituents across different habitats and the potential influence of harvesting times on the accumulation of these constituents [16].…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%